Literature and Geography - Czapliński, Przemysław (Porównania, 2020)
This article proposes to treat literature as a template of the collective imagination. The basis for discussion is Polish prose from 1986–2016, with the main thesis being that Polish culture has reached the limits of geographical imagination. This is the result of Poland withdrawing from the larger structures to which it once belonged or to which it aspired (its diminishing presence in the European Union, the disappearance of Central Europe, delayed efforts to pursue the Scandinavian model of the state and civic culture, the destruction of relations with Lithuania, Belarus and Ukraine). Weakening or breaking ties with neighboring countries has led to isolation from all four sides. In order to get out of this impasse, it is necessary to develop new narratives that would link Poland with the neighboring cultures and would once again put our country back on the European map.